ANALISIS DAMPAK TARIKAN KENDARAAN DI PUSAT PERBELANJAAN CIREBON SUPER BLOCK KOTA CIREBON - Gary Raya Prima; Ryan Rivandi Pratama; Nina Herlina (Faculty of Engineering, Planning and Architecture, Winaya Mukti University, 2021)
Cirebon Super Block (CSB) Mall is a fairly solid place to sell goods in the city of Cirebon. With the establishment of the Cirebon Super Block (CSB) in the city of Cirebon, it will cause vehicle traction on the roads around the Cirebon Super Block (CSB) and will increase traffic volume. The construction of these shopping centers also has an impact on the surrounding road sections, namely in the form of a reduction in the level of service (LOS) which at a certain point will cause congestion. This is due to increased movement due to increased commercial activities or activities on these roads. Travel attraction is a modeling stage that estimates the amount of movement originating from a zone or land use and the amount of movement attracted to a land use or zone. Cirebon Super Block Mall has generated quite a lot of vehicle traction on the Cipto Mangunkusumo road. The biggest vehicle pull on Jalan Cipto Mangunkusumo occurred on weekends (Sundays) at 17.00-18.00 which was 687.6 pcu / hour where the volume of vehicles on Jalan Cipto Mangunkusumo 3086.4 pcu / hour had an impact of 22.3%.